MAPPING SERVICE RECOVERY STRATEGY RESEARCH: A SYSTEMATIC REVIEW - Carmen Mandey; Deske W. Mandagi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Service recovery has become an important research area as organizations seek effective strategies to address service failures and maintain customer relationships. This study conducts a bibliometric analysis to examine the intellectual structure and thematic evolution of service recovery research. Initially, 258 publications were retrieved from the Scopus database, and after screening, 182 studies were retained for analysis. Using keyword co-occurrence and overlay visualization techniques, the results identify six major research clusters: (1) justice, satisfaction, and perceived fairness; (2) customer behavior, loyalty, and forgiveness; (3) service failure and recovery processes; (4) employee roles and organizational responses; (5) hospitality and tourism applications; and (6) digital platforms, artificial intelligence, and online service contexts. Early studies focused on justice perceptions and complaint management in service failures, while later research expanded to behavioral outcomes, organizational capabilities, and industry applications. Recent studies increasingly explore digital service environments, including online reviews, social media, and AI-enabled service recovery. These findings map the intellectual structure of service recovery research and highlight emerging directions for technology-driven service recovery and customer relationship management.